The Versatile Roles of Cancer-Associated Fibroblasts in Colorectal Cancer and Therapeutic Implications - Deng, Longfei; Jiang, Nianfen; Zeng, Jun; Wang, Yi; Cui, Hongjuan (Frontiers in Cell and Developmental Biology, 2021)
The tumor microenvironment (TME) is populated by abundant cancer-associated fibroblasts (CAFs) that radically influence the disease progression across many cancers, including the colorectal cancer (CRC). In theory, targeting CAFs holds great potential in optimizing CRC treatment. However, attempts to translate the therapeutic benefit of CAFs into clinic practice face many obstacles, largely due to our limited understanding of the heterogeneity in their origins, functions and mechanisms. In recent years, accumulating evidence has uncovered some cellular precursors and molecular markers of CAFs and also revealed their versatility in impacting various hallmarks of CRC, together helping us to better define the population of CAFs and also paving the way towards their future therapeutic targeting for CRC treatment. In this review, we outline the emerging concept of CAFs in CRC, with an emphasis on their origins, biomarkers, prognostic significance, as well as their functional roles and underlying mechanisms in CRC biology. At last, we discuss the prospect of harnessing CAFs as promising therapeutic targets for the treatment of patients with CRC.